Double-band hysteresis current-controlled single-phase shunt active filter for switching frequency mitigation - Komurcugil, Hasan (Elsevier Sci Ltd, 2015)
This paper proposes a double-band hysteresis current-control (DBHCC) scheme for single-phase shunt active filters. The idea behind this scheme is to enable access to the zero level of the active filter's input voltage so that a switching device is only switched during a half-cycle, while it remains either on or off during the other cycle. Average switching frequency expressions of the conventional single-band hysteresis current-control (SBHCC) and DBHCC schemes have been derived. It is shown that the DBHCC results in a much lower average switching frequency than that of SBHCC scheme leading to reduced switching losses for the same parameter values. It is also worth to note that the DBHCC scheme offers a smaller total harmonic distortion (THD) of the source current for small hysteresis band values. The steady-state and transient performance of the proposed control scheme has been tested through simulations under a diode bridge rectifier load, a diode bridge rectifier with RL load and a triac-controlled resistive load. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Shunt active filters; Hysteresis current-control; Switching frequency